2016
DOI: 10.3109/09546634.2015.1115819
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, placebo-controlled, dose-escalation study of the safety and efficacy of INCB039110, an oral janus kinase 1 inhibitor, in patients with stable, chronic plaque psoriasis

Abstract: INCB039110 produced significant improvements in sPGA, demonstrating proof of concept in chronic plaque psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
61
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 22 publications
2
61
0
Order By: Relevance
“…There were no incidences of anaemia or thrombocytopenia during this study and the incidence of infections was low. Changes in lipid parameters were observed in this study, as has been reported in some studies with other JAK inhibitors . The most dramatic effects on HDL and LDL cholesterol were observed in subjects receiving PF‐04965842 BID.…”
Section: Discussionsupporting
confidence: 87%
“…There were no incidences of anaemia or thrombocytopenia during this study and the incidence of infections was low. Changes in lipid parameters were observed in this study, as has been reported in some studies with other JAK inhibitors . The most dramatic effects on HDL and LDL cholesterol were observed in subjects receiving PF‐04965842 BID.…”
Section: Discussionsupporting
confidence: 87%
“…In this study, infections occurred more frequently in the PF‐04965842 vs. placebo groups, but there were no serious infections or bleeding events related to neutropenia or thrombocytopenia, respectively. Infections were also reported more frequently for patients treated with INCB039110 compared with placebo, but not for those treated with GSK2586184 compared with placebo . Recent data from studies of tofacitinib treatment in patients with psoriasis showed that nasopharyngitis and upper respiratory tract infections were the most frequent infections and the authors noted increased occurrence of herpes zoster …”
Section: Discussionmentioning
confidence: 67%
“…Dose‐dependent reduction in psoriasis severity has been reported with two other JAK1 inhibitors. Treatment with INCB039110 resulted in reductions from baseline in static PGA at day 28 (mean 22·2–42·4% for 100 mg OD, 200 mg OD, 200 mg TD and 600 mg OD, respectively) . Similarly, dose‐dependent changes from baseline in PASI scores were observed following 12 weeks of treatment with GSK2586184 100 mg TD, 200 mg TD and 400 mg TD .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations